Analisis Sebaran Spasial Kerentanan Bencana Banjir di Kota Medan Tahun 2023 - Juliana, Asima; Thoha, Achmad Siddik; Lubis, Satia Negara (Jurnal Serambi Engineering, 2025)
Flooding is one of the environmental problems that often occur in Medan City due to rapid urban development and land use change. This research aims to analyse the spatial distribution of flood vulnerability in Medan City based on the parameters of land use, slope, soil type, geology, distance from river and rainfall. The methods used in this research include Geographic Information System (GIS) analysis and weighting of flood vulnerability parameters using the scoring method. The data used included Sentinel 2 imagery for land use, DEM data for slope, CHRIPS for rainfall and SHP data for soil type and geology. The spatial distribution of flood vulnerability in Medan City shows a concentration in the southwest and central parts of the city. The spatial distribution of flood vulnerability is mostly at the high - very high vulnerability level, namely in the Belawan Sicanang area of 1,047.07 ha. high vulnerability level, namely in the Belawan Sicanang area of 1,047. 07 ha with a percentage of 12%, Martubung village area of 1,032 ha with a percentage of 11%, Kelurahan Besar area of 1,013 ha with a percentage of 11% and Pekan Labuhan village area of 1,022 ha with a percentage of 11%. Ha with a percentage of 11%. This research is expected to be a suggestion for spatial distribution developed as an early warning system for flood impacts in Medan City.